Anxiety and Religious Literacy: An Intercorrelation Analysis in the Context of Post-Teaching Practice Catechesis - Lukas Ahen; Angga Satya Bhakti; Cenderato Cenderato (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
This scholarly inquiry examined the interrelationship between anxiety levels and religious literacies in relation to pedagogical and catechetical methodologies among 115 students in their seventh semester of post-Teaching Practice at STAKat Negeri Pontianak. Quantitative data, derived from validated questionnaires comprising 21 items, alongside qualitative data obtained from interviews, were subjected to analysis via the One-Sample Kolmogorov-Smirnov test and simple regression techniques. The results of normality tests corroborated the appropriateness of employing parametric statistical methodologies (p > 0.05). The regression analysis indicated a statistically significant positive influence of anxiety on religious literacies (F = 29.082, p < .001), thereby suggesting that increased levels of anxiety correlate with enhanced understanding of catechism. In addition, correlation analysis conducted among 26 participants revealed a robust positive correlation (r = 0.740, p < .001) between anxiety and religious literacies, implying a potential association between a more profound comprehension of religious doctrines and elevated anxiety, which may be attributable to the introspective characteristics of catechism or the propensity of anxious individuals to seek significance within religious teachings.